Time-motion analysis and physiological responses to karate official combat sessions: is there a difference between einners and defeated karatekas? - Chaabene, H.; Franchini, E.; Miarka, B.; Selmi, M. A.; Mkaouer, B.; Chamari, K. (International Journal of Sports Physiology and Performance, 2014)
Purpose: The aim of this study was to measure and compare physiological and time-motion variables during karate fighting and to assess eventual differences between winners and defeated elite karatekas in an ecologically valid environment. Methods: Fourteen elite male karatekas who regularly participated in national and international events took part in a national-level competition. Results: There were no significant differences between winners and defeated karatekas regarding all the studied variables. Karatekas used more upper-limb (76.19%) than lower-limb techniques (23.80%). The kisami-zuki represented the most frequent technique, with 29.1% of all used techniques. The duration of each fighting activity ranged from post) elicited during karate fighting was 11.18 ± 2.21 mmol/L (difference between Lapre and Lapost = 10.01 ± 1.81 mmol/L). Mean heart rate (HR) was 177 ± 14 beats/min (91% ± 5% of HRpeak). Karatekas spent 65% of the time exercising at HR >90% of the individual HRpeak. Conclusion: Karatekas predominantly use upper-limb karate techniques. Karate`s nature is intermittent, with fighting activities representing ~6% of total combat`s duration and ~84% of actions lasting less than 2 s, with ~21-s mean time interval in between. Kumite combat sessions induced high La and near-maximal cardiovascular strain. Other key success factors should be investigated to properly discriminate winners and defeated athletes.